2019
DOI: 10.12944/crnfsj.7.3.14
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intrinsic and Extrinsic Factors on the Storage Stability of Sardine Oil

Abstract: Oil extracted from pelagic fishes, rich in n-3 polyunsaturated fatty acids (PUFA) like Eicosapentaenoic acid and Docosahexaenoic acid, have numerous health benefits. The oil also contains impurities like di- and mono glycerides, free fatty acids, phospholipids, unsaponifiable matter, metal ions and volatile compounds. Most of these impurities are removed by refining process without affecting valuable n-3 PUFA. However, due to the presence of residual impurities, environmental factors and higher degree of unsat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Some studies revealed that PL has the ability to prevent oxidation in o/w emulsion (Cardenia et al, 2011) and bulk oil (Cui et al, 2014;Charanyaa et al, 2019). In this study, crude PL capability from PPF and its fractions to inhibit oxidation was evaluated in bulk soybean oil.…”
Section: Antioxidant Activitymentioning
confidence: 94%
“…Some studies revealed that PL has the ability to prevent oxidation in o/w emulsion (Cardenia et al, 2011) and bulk oil (Cui et al, 2014;Charanyaa et al, 2019). In this study, crude PL capability from PPF and its fractions to inhibit oxidation was evaluated in bulk soybean oil.…”
Section: Antioxidant Activitymentioning
confidence: 94%